2012
DOI: 10.1038/ejcn.2012.3
|View full text |Cite
|
Sign up to set email alerts
|

Estimating dual-energy X-ray absorptiometry-derived total body skeletal muscle mass using single-slice abdominal magnetic resonance imaging in obese subjects with and without diabetes: a pilot study

Abstract: BACKGROUND/OBJECTIVES: Single-slice abdominal computed tomography or magnetic resonance imaging (MRI) performed to measure visceral adipose tissue in individuals with obesity and diabetes mellitus can also image skeletal muscle. The aim of this study was to validate a method developed in cancer patients using a single abdominal cross-sectional image to estimate fat-free mass (FFM) and appendicular lean tissue mass index (LTMI), a total body skeletal muscle mass surrogate, in an obese cohort of subjects with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…The total area of skeletal muscle of a single cross-sectional image at the L4-5 interface, normalized for height, was found to be highly correlated with both total body skeletal muscle (r = 0.9) and adipose tissue (r = 0.94) in a study in which whole-body magnetic resonance images were used as the reference standard (15). Additional investigators validated single-section cross-sectional muscle measurement at various levels as an accurate estimate of muscle mass (14). At the level of the L4-5 interface, the Eclipse CT ranger tool (https:// github.com/rexcardan/AverageHU_ES-API) was used to automatically generate a structure that contained all voxels with attenuation between 229 HU and 150 HU on the section (19).…”
Section: End Point Definitions and Statistical Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The total area of skeletal muscle of a single cross-sectional image at the L4-5 interface, normalized for height, was found to be highly correlated with both total body skeletal muscle (r = 0.9) and adipose tissue (r = 0.94) in a study in which whole-body magnetic resonance images were used as the reference standard (15). Additional investigators validated single-section cross-sectional muscle measurement at various levels as an accurate estimate of muscle mass (14). At the level of the L4-5 interface, the Eclipse CT ranger tool (https:// github.com/rexcardan/AverageHU_ES-API) was used to automatically generate a structure that contained all voxels with attenuation between 229 HU and 150 HU on the section (19).…”
Section: End Point Definitions and Statistical Methodsmentioning
confidence: 93%
“…While the purpose of treatment-planning CT is to delineate target volumes and assess tissue attenuation to perform accurate dose calculations, additional anatomic information is obtained that may be of clinical value. A number of reports have confirmed that bone mineral density (BMD) (11)(12)(13) and total body muscle mass (14,15) can be estimated accurately from abdominal and pelvic images obtained for other reasons. Osteopenia (16) and sarcopenia (17,18) have both been associated with an increased risk of noncancer death in a number of different populations.…”
Section: Ct Metrics Of Body Compositionmentioning
confidence: 99%
“…), hence, reducing inter‐observer variability. Furthermore, manual tracing of image sets comprised of several axial slices was performed, thus allowing exact tracking of muscles based on the traced boundaries (Baker et al ., ; Taguchi et al ., ). Lastly, the manual tracing method used in this study compensates for any potential image artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…The image analysis of trunk muscles was performed using axial plane images at the third lumbar vertebrae (L 3 ) (Zhou et al ., ; Shen et al ., ; Mourtzakis et al ., ; MacDonald et al ., ; Baker et al ., ). The inter‐reader and intrareader reproducibility of manual analysis of body composition using MRI scans have shown reliability of this approach (Maurovich‐Horvat et al ., ; MacDonald et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“… 20 Analysis of a single cross-sectional image from CT or magnetic resonance imaging (MRI) provides an accurate estimate of total body FFM and FM, as well as visceral FM and subcutaneous FM. 21 , 22 , 23 , 24 We have validated this technique in patients with Crohn's disease, 25 with high degrees of correlation between CT or MRI and DXA.…”
Section: Introductionmentioning
confidence: 97%